(untitled) (CIPEEX, 2026)
The research aims to analyze the concepts of incapacity, disability, and impairment in the context of granting social security benefits to individuals with mental disorders. The aim is to determine, in light of the intersection between law and psychopathology, how the process for proving the need for the benefit occurs. The research uses qualitative scientific methodology in the bibliographic modality, including the use of instruments such as the ICD-11 and DSM-V-TR, to analyze aspects related to nosology and diagnosis. Therefore, the study of this topic is essential, considering the lack of precise legislation in law.